Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Conférence «La construction de la légitimité intellectuelle des femmes» - Charron, Hélène (2014)
Conférence d'ouverture du colloque « Les femmes dans les sciences humaines : étudier, enseigner, travailler, militer » Date de l’événement : 20 mars 2014 Hélène Charron, chercheure au Conseil du statut de la femme, chercheure associée à la Chaire Claire-Bonenfant de l’Université Laval, et chargée de cours en études féministes et en sociologie.
Keywords: approches et analyses; discipline; discours dominant; genre; histoire et politique; identités LGBTQIA2+; milieux universitaires; sciences; sciences humaines; sciences sociales; sociologie; systèmes d'oppressions; thématiques

La valence différentielle des sexes, création de l'esprit humain archaïque - Héritier-Augé, Françoise; Molinier, Pascale (Nouvelle revue de psychosociologie, 2014)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; discours dominant; europe; histoire et politique; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques